Racial Discrimination in Grisham's "A Time to Kill": Racial Discrimination, John Grisham, Black And White, Novel - Onibala, Ralf; Andries, Fivy; Rorintulus, Olga (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study aims to reveal the racial discrimination as seen in the novel A Time To Kill by John Grisham. In completing this study material, the writer uses qualitative research because the data are in the type of words and quotation rather then numbers. There are two source the writer used, that is from the novel and internet. Sociological approach is applied in order to analyse the data. The finding shows that racial discrimination in settlement, discrimination of social relation in groups, supporting rules for whites, influence of parents belief, the unequal treatment for public services, and the disharmony relation among blacks and whites.. Black are seen as a lowly race, and segregated from whites. As seen in the trial black right are oppressed while white are in an adventedges that leads to struggle for justice in the time of unequality. These rules are made to segregate black from th whites and vice versa. Parents influence their children to assume that black are dirty, low intellect, and violent. Black people are not treated normally in public place. They also feel a decrease in confidence. They are discriminated in the society, in education area, in the courthouse also in social relation.